2001
DOI: 10.1159/000047158
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Heater Responses during Transition between Radiant and Incubator Thermal Environment in Newborn Preterm Lambs

Abstract: Objective: Although both incubators and radiant warmer beds can provide thermal support to infants in the neonatal intensive care unit, the transition between devices can be a stressful event. The goal of this study was to evaluate a new device that combines these methods of warming and converts between them without requiring physical movement of the infant. Study Design: Twin preterm lambs received thermal support from a radiant warmer bed and an incubator (control), or from the VersaletTM 7700 Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Further investigations regarding incubator temperature stability, rapid changes (e.g. on opening and closing the incubator door) in test response time, overshoot and long-term stability as reported by Touch et al [11] , and clinical interventions (phototherapy, thoracic drains, blood sampling, continuous tc-bloodgas monitoring and handling of hygiene) are required before this method can be put into clinical use in premature human infants. However, the results of the present study suggested the possibility of using a liquid incubator to control the temperature of premature infants.…”
Section: Discussionmentioning
confidence: 89%
“…Further investigations regarding incubator temperature stability, rapid changes (e.g. on opening and closing the incubator door) in test response time, overshoot and long-term stability as reported by Touch et al [11] , and clinical interventions (phototherapy, thoracic drains, blood sampling, continuous tc-bloodgas monitoring and handling of hygiene) are required before this method can be put into clinical use in premature human infants. However, the results of the present study suggested the possibility of using a liquid incubator to control the temperature of premature infants.…”
Section: Discussionmentioning
confidence: 89%
“…Modern neonatal incubators offer the patient a microprocessor controlled heated and humidified environment and more advanced options such as heliox [2]. Despite advances in design, disruptions in the integrity of the internal environment of the incubator could threaten the fragile infant [3][4][5].…”
Section: Introductionmentioning
confidence: 99%